Experiences women's bicycling activists in the promotion of biciculture in Santiago de Chile - Dri Manfiolete, Sandra Soledad Troncoso Robles; Manfiolete Troncoso, Leandro Dri [UNESP]; Zarate Fernandez, Amalia Ortiz de (Federacion Espanola Asoc Docentes Educacion Fisica-feadef, 2023)
The objective this article presenting experiences womens cycleactivist leaders who promote bicycling culture in Santiago de Chile. The methodology implemented is situated phenomenon (Phenomenology). The selection criteria for the five women interviewed: a) being a cycling activist; b) participating actively in citizen organizations; c) developing political-pedagogical projects related promotion bicycling. The results show two thematic categories and six units meaning: 1) Cycling safely in the city made up equitable urban planning; perception of urban female bicyclists; and education for the use bicycles; 2) Promotion of bicycling made up citizen participation in institutional policy, creation of collaborative spaces and organization bicycling events. We consider Chilean cycle-activist female discourse in relation social practice urban cycling seeks integrating various factors through promotion bicycling.
Keywords: bicycling; active commuting; social construction of gender; human rights; public policy